Poly (butylene succinate)/polyethersulfone/poly (ethylene glycol) membrane: influence of additive molecular weight and concentration on morphology, properties, and performance of the membrane. Issue 36 (1st August 2016) - Ghaffarian, Vahideh; Mousavi, Seyed Mahmoud; Bahreini, Masoumeh; Chamani, Hooman
Abstract: In the present study, characteristics of poly (butylene succinate) (PBS)/polyethersulfone (PES)/poly (ethylene glycol) (PEG) membrane were described in terms of the presence of hydrophilic and biodegradable additive of PEG in two different levels for concentration and molecular weight. The membranes were prepared using immersion precipitation technique at two coagulation bath temperatures (CBT) of 0 and 25°C. Experiments showed that the examined levels for PEGs changed the membrane morphology in both surface and cross-sectional structures. Moreover, the presence of PEGs improved the final membrane wettability, tensile strength, and biodegradability. According to Fourier transform infrared analysis, no chemical bond was formed between PEG and PBS/PES. The variations of the membrane morphology affected the fluxes for both pure water and wastewater. As a result, the highest fluxes were obtained for the membrane with 7 wt.% of PEG400 prepared at CBT of 25°C.